The Transition to Renewable Energy Sources as a Threat to Resource Economies - Udalov, Ivan (International Journal of Energy Economics and Policy, 2021)
Changes in global development benchmarks, the gradual depletion of natural resources, as well as global climatic changes are forcing economic actors around the world to look for alternative methods of energy production. The transition to them can be difficult due to the high cost of the produced energy and pressure from states and corporations specializing in the extraction of classical energy sources. The article is devoted to the study of the transition to renewable energy. The article uses a statistical analysis of indicators and makes a conclusion about the relationship between development trends. It is clear with a fair amount of confidence that the positive dynamics of the renewable energy market is leading to changes in the energy market in the USA, Europe and some other parts of the world. Keywords: renewable energy sources, export and consumption of fossil energy, alternative energy, resource economies. JEL Classifications: C10, E21, E23, Q41, Q42 DOI: https://doi.org/10.32479/ijeep.10902